The withdrawal from Afghanistan: Successful end of another NATO mission? - Zirojević-Fatić Mina; Korać Srđan (Međunarodni Problemi)
The paper examines whether and to what extent the primary objectives of the NATO-led International Security Assistance Force’s mission, which has conducted security and stability operations throughout Afghanistan, have been achieved. The authors focus their analysis on establishing political institutions and effective public policy implementation as well as on developing and training Afghan military, police and other security capacities - all aimed at providing secure environment for sustainable economy and daily life in the country. The paper discusses the results of the NATO-led international mission in the context of geopolitics and the geostrategic position of Afghanistan as a Middle East country and its place in the longstanding U.S. Foreign Policy objectives in the region. The authors employ the dynamic research approach in order to cover the topic within a decade time frame. The authors conclude that the NATO-led International Security Assistance Force’s mission has failed to fully meet the political objectives, while the security objectives have been achieved only to a lesser extent.